2015
DOI: 10.1590/0034-7167.2015680624i
|View full text |Cite
|
Sign up to set email alerts
|

Baixo peso ao nascer em município da região sudeste do Brasil

Abstract: knowledge of this evidence favors planning the care provided by defining strategies to reduce it and consequently improve maternal and infant health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
2
6
0
5
Order By: Relevance
“…The odds of infants born from mothers whose age < 20 years were nearly two times more risk to have LBW. This finding supported by other studies conducted in Nigeria [ 75 ] and Brazil [ 76 ]. This age group might be teenage pregnancy that mostly gives LBW infants usually due to unplanned and/or unwanted pregnancy, which leads to less attention to nutritional value and health care services utilization [ 77 ], lack of fair jobs, and a low level of knowledge of pregnancy’s danger sign and major risk factors [ 78 ] might be attributed to LBW in teenage pregnancy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The odds of infants born from mothers whose age < 20 years were nearly two times more risk to have LBW. This finding supported by other studies conducted in Nigeria [ 75 ] and Brazil [ 76 ]. This age group might be teenage pregnancy that mostly gives LBW infants usually due to unplanned and/or unwanted pregnancy, which leads to less attention to nutritional value and health care services utilization [ 77 ], lack of fair jobs, and a low level of knowledge of pregnancy’s danger sign and major risk factors [ 78 ] might be attributed to LBW in teenage pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…The odds of being premature birth was six times higher risk to be below normal birth weight. The finding from another study in India [ 87 ], Iran [ 12 ], and Brazil [ 76 ] also showed the positive association between premature birth and LBW. The several organ systems of human fetus usually become mature by the end of 37 weeks of gestation [ 88 ].…”
Section: Discussionmentioning
confidence: 68%
“…In the comparison with the study carried out in the city of São Paulo (SP), ( 8 ) the pregnant women of this sample were younger (24.0 years versus 27.5 years), had less cesarean sections (41.0% versus 56.5%), and a similar proportion of single gestations (98.5% versus 97.3%). Relative to the study on the spatial distribution of liveborns in the same city in 2008, our sample showed smaller proportions of pregnant women with up to 11 years of schooling (53.4% versus 58.2%), and similar extent of primigravidae (51.6% versus 53.9%).…”
Section: Discussionmentioning
confidence: 85%
“…The proportion of LBW observed (7.6%) is below that reported in literature. In the city of São Paulo (SP), between 2007 and 2013, the rates of LBW varied from 9.6% to 9.8%; ( 8 ) in the city of Divinópolis (MG), it ranged from 8.9% to 9.2%, between 2008 to 2011; ( 9 ) and in the city of Taubaté (SP), between 2006 and 2010, it varied from 9.3% to 9.8%. ( 10 ) In these comparisons, one should take into account that in the last two studies, twin birth were excluded from analyses, which could have influenced the proportions of LBW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation